LANGUAGE PROFICIENCY TEST DESIGN FOR A GROUP OF MILITARY PILOTS: CRITERIA, CONSTRUCT AND PURPOSE - E Silva, Ana Lígia Barbosa de Carvalho [UNESP] (University of Nis, 2023)
Despite the growing number of studies devoted to Aeronautical English, the role of language assessment to military pilots seems to be largely overlooked. To narrow this gap, this study aims at putting forward some findings of a broader study (Silva 2022)) which comprises a test design for a group of pilots from the Air Demonstration Squadron (EDA) of the Brazilian Air Force (FAB). Test design refers to the definition of crucial aspects of a test, prior to its development, such as: i) the criterion, or the communicative behavior expected in the target situation; ii) the construct, i.e., what the test is intended to assess; and iii) the purpose, which is mainly related to the reason why the test is designed and the interpretation and uses of its results. Language Assessment for Professional Purposes (LAPP) (Knoch and Macqueen 2020) is the main theoretical framework that guided this “Mixed Methods Case Study Design” work (Creswell and Clark 2018). Results indicate that the design of an English test for EDA pilots, based on a needs analysis, should be wide enough to encompass the use of Aeronautical English (phraseology and plain English for radiotelephony communications) and a more general language. As for the test purpose, data analyses indicate that test results could be useful in the selection of pilots who would be more suited to fly together as crew members. The expected contribution of the study is to provoke reflections on the main characteristics of an English proficiency test for military pilots, without losing sight of the commonalities it may have with language needs for other pilots around the world.
Keywords: Aeronautical English; ESP; language assessment for professional purposes (LAPP; language proficiency; pilots; test design